Brain death‐induced lung injury is complement dependent, with a primary role for the classical/lectin pathway. Issue 3 (4th September 2020) - van Zanden, Judith E.; Jager, Neeltina M.; Seelen, Marc A.; Daha, Mohamed R.; Veldhuis, Zwanida J.; Leuvenink, Henri G.D.; Erasmus, Michiel E.
Abstract: In brain‐dead donors immunological activation occurs, which deteriorates donor lung quality. Whether the complement system is activated and which pathways are herein involved, remain unknown. We aimed to investigate whether brain death (BD)‐induced lung injury is complement dependent and dissected the contribution of the complement activation pathways. BD was induced and sustained for 3 hours in wild‐type (WT) and complement deficient mice. C3 −/− mice represented total complement deficiency, C4 −/− mice represented deficiency of the classical and lectin pathway, and factor properdin (P) −/− mice represented alternative pathway deficiency. Systemic and local complement levels, histological lung injury, and pulmonary inflammation were assessed. Systemic and local complement levels were reduced in C3 −/− mice. In addition, histological lung injury and inflammation were attenuated, as corroborated by influx of neutrophils and gene expressions of interleukin (IL)‐6, IL‐8–like KC, TNF‐α, E‐selectin, and MCP‐1. In C4 −/− mice, complement was reduced on both systemic and local levels and histological lung injury and inflammatory status were ameliorated. In P −/− mice, histological lung injury was attenuated, though systemic and local complement levels, IL‐6 and KC gene expressions, and neutrophil influx were not affected. We demonstrated that BD‐induced lung injury is complement dependent, with a primary role for the classical/lectin activation pathway. Abstract : In a mouse model, brain death–induced lung injury is complement‐dependent, elucidating a primary role for the classical/lectin complement activation pathway.